Complications in Maxillary Local Anesthesia - Chisci Glauco (Global Journal of Anesthesiology - Peertechz Publications, 2015)
One aspect of oral pathology and maxillofacial not to be overlooked in the anesthesiological approach to the patient are complications due to local anesthesia in maxillary bone.   Main procedures of local anesthesiology involve the greater palatine nerve, the infra-orbitary nerve and the posterior superior alveolar nerve: all of these nerves derive from the second sensitive branch of the trigeminal nerve.